The Impact of Environmental Performance Rating and Disclosure : An Empirical Analysis of Perceptions by Polluting Firms’ Managers in China - Jin, Yanhong; Wang, Hua; Wheeler, David (2012)
Environmental performance rating and disclosure has emerged as a substitute or complement for traditional pollution regulation, especially in developing countries. Using data from China's Green Watch program, this study extends previous research on performance rating and disclosure by considering firms' perceptions of public and market responses to their ratings. The results suggest that the Green Watch has significantly increased market and stakeholder pressures on managers to improve their firms environmental performance. More specifically, controlling for the characteristics of locations, firms, and individual managers, the analysis finds that firms with better ratings perceive positive impacts on market competitiveness, overall market value, and relationships with different stakeholders, while the firms with bad ratings are more likely to perceive deterioration. Among these factors, managers perceive a more active role for markets than for stakeholder relations.